The Application of the Number Head Together (NHT) Type Cooperative Learning Model in Science Learning - Haerana; Suwandayani, Beti Istanti; Waluyo, Lud (The Indonesian Institute of Science and Technology Research, 2025)
The application of learning models plays a very important role. This research aims to analyze the effectiveness of the NHT model in learning science and technology in grade 5 at a Madrasah Ibtidaiyah (an elementary religious-based school). The method used is a qualitative-descriptive study with a case study approach. The results show that the application of the NHT model is able to increase active participation and student learning outcomes. If the methods used in education are not appropriate, then achieving educational goals will be difficult to realize. The type of research used is qualitative. The qualitative research approach is concerned with human behavior and roles in research proposals. As a result, it is hoped that it will be easier for researchers to develop approaches and change their research targets so that they can be applied in the field. Physical fitness because it will influence learning outcomes and individual social adjustment. Students must also be seen as mentally prepared, referring to intelligence, high memory, fulfilled needs, desire or motivation to learn, ability to concentrate and pay attention, then readiness of learning materials as learning materials, exercise books, supported by various reading sources. This book provides information and helps students answer questions related to the teacher's lessons.